Physiological benefits of warm-up - Shellock, F. G. (The Physician and Sportsmedicine, 1983)
Changes derived from a warm-up that is specifically designed for endurance events have been documented. These alterations produce a higher percentage of energy production from aerobic processes because of the facilitation of aerobic mechanisms that occurs after passive warm-up or rest. Ingjer and Stromme (1979) verified these benefits as well as finding that lactic acid levels were lowered during work and in recovery. Shellock (1983) listed the changes. 1.The breakdown of oxyhemoglobin for the delivery of oxygen to the working muscle is facilitated. 2.The release of oxygen from myoglobin is increased. 3.The activation energy for vital cellular metabolic chemical reactions is lowered. 4.Muscle viscosity is reduced, resulting in an improvement in mechanical efficiency. 5.Nervous impulses travel more rapidly and the sensitivity of nerve receptors is augmented. 6.Blood flow to the muscles is increased. 7.Injuries related to the muscles, tendons, ligaments, and other connective tissues may be reduced. 8.The cardiovascular response to sudden, strenuous exercise is improved. Implication: Aerobic endurance warm-up activity better prepares the body for aerobic endurance performance.